EVALUATION OF BIOCONTROL POTENTIALS OF CRUDE EXTRACTS OF SOIL FUNGI ON WEEDS, Amaranthus hybridus AND Phyllanthus amarus - Fawole, Oluyemisi Bolajoko; Yahaya, James Ukwumonu (Journal of Agricultural Sciences (Belgrade), 2017)
In a pot experiment, two fungal strains from soil, Aspergillus fumigatus and Penicillium citrinum were evaluated for their mycoherbicidal properties on Amaranthus hybridus and Phyllanthus amarus using the biomass reduction method. The experiment was set up in a Completely Randomised Block Design made up two weed species exposed to 20 treatments which consisted of the concentrated crude extracts of Aspergillus fumigatus and Penicillium citrinum at five levels each in three replications. The percentage biomass yields of Amaranthus hybridus and Phyllanthus amarus were determined at 1, 3, 5 and 7 days after application and biomass reductions were calculated. Data collected were subjected to Analysis of Variance and significant means separated using Duncan Multiple Range Test. Infections of the weeds occurred within 48 hours after the application of the crude extract treatments. Significant differences (p ≤ 0.001) were observed in the percentage biomass yields of the two weed species especially at the highest inocula concentration (5% w/v) of the crude extracts. The percentage biomass yields of Amaranthus hybridus were 88.58% and 88.91% while 69.79% and 81.34% were recorded for Phyllanthus amarus after the application of the concentrated extracts of Aspergillus fumigatus and Penicillium citrinum respectively. The study established that the concentrated crude extracts of both Aspergillus fumigatus and Penicillium citrinum have the potentials for use as extracts of Penicillium citrinum had the greatest impact on the biomass yields of the two test weeds.